GAYA KEPEMIMPINAN TERHADAP KINERJA PADA SD NEGERI JATISARI II KOTA BEKASI - Kartika Yuliantari; Elita Mega Hinandar (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Principal leadership has a strategic leadership style in realizing successful implementation and management of education. This study aims to assess the leadership style of principals on teacher performance. Data collection was carried out through questionnaires and carried out in November to all SD Negeri Jatisari II teachers in Bekasi City. SPSS 23 is used to analyze data. Saturated Sample Method was carried out in this study. The results show that the Leadership Style has very strong results. The results of the coefficient of determination in accordance with R Square amounted to 0.866 teacher performance influenced by leadership style. Simple linear regression analysis between Leadership Style on Teacher Performance is Y = 1.045 + 0.968 (X = Leadership Style and Y = Teacher Performance. Thus the direction of leadership style towards teacher performance is one-way positivity. Respondents' assessment of leadership style of SD Jatisari Elementary School II is quite good, but it needs to be improved in its leadership style, given the importance of leadership style in accordance with existing rules.